Postoperative outcomes of varicocelectomy and impact of on infertility among sample of patient in Baghdad, Iraq - Al-Gaysi, Abdulraheem Ali Bakheet; Masaoodi, Sami Hamad Oleiwi; AbuAlmaali, Haider A. (International Surgery Journal, 2018)
Background: Varicocele is the possible cause of 35% primary infertility, 70-80 % secondary and it is associated with progressive and duration dependent decline in testicular function. The aim of this study was to assess the postoperative outcome of varicocelectomy and determine positive impact on ability to reduce infertility. Methods: Twenty-five infertile male patients with varicocele, their age range from (20-40) year mean (30 year), were included and evaluated prospectively and retrospectively in Al-Karama teaching hospital from 2013-2016. Patients were divided in present study according to age of patient, degree of varicocele, duration of infertility and type of infertility. Site of varicocele was either left unilateral or bilateral. All the patients were treated surgically using three different approaches; Retroperitoneal approach, Inguinal and Sub inguinal approach and Scrotal approach. Results: It is noticeable that scrotal swelling was the most frequent complication and infection was the second highest. According to the age of patient, it was shown that beneficial effect of the Varicocelectomy was most favourable among younger age group. It is observables that favourable outcome was better among those with secondary fertility. It was found that grade III varicocele was associated with better outcome in terms of pregnancy and sperms motility. Conclusions: Scrotal swelling and infection was the most highly reported complication. Favourable effect of the Varicocelectomy was most among younger age group, secondary fertility and grade III varicocele.